2009
DOI: 10.1111/j.1475-6773.2008.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Survey Mode, Patient Mix, and Nonresponse on CAHPS® Hospital Survey Scores

Abstract: Objective. To Study Design/Data Collection/Extraction Methods. We estimated mode effects in linear models that predicted each HCAHPS outcome from hospital-fixed effects and patient-mix adjustors. Principal Findings. Patients randomized to the telephone and active interactive voice response (IVR) modes provided more positive evaluations than patients randomized to mail and mixed (mail with telephone follow-up) modes, with some effects equivalent to more than 30 percentile points in hospital rankings. Mode eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
309
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 297 publications
(330 citation statements)
references
References 19 publications
19
309
2
Order By: Relevance
“…While it is possible that survey methodology could explain the differences between the groups, previous work has shown that mailed surveys tend to score lower, thus biasing our results towards a finding of lower dissatisfaction for children with SCD [15]. Likewise, the surveys were not conducted over identical time periods; however, as there were no significant changes in scores over time for the hospital survey, combining the years for the control groups should not have affected the comparisons and still allowed for more power in analyzing differences between the groups.…”
Section: Discussioncontrasting
confidence: 47%
“…While it is possible that survey methodology could explain the differences between the groups, previous work has shown that mailed surveys tend to score lower, thus biasing our results towards a finding of lower dissatisfaction for children with SCD [15]. Likewise, the surveys were not conducted over identical time periods; however, as there were no significant changes in scores over time for the hospital survey, combining the years for the control groups should not have affected the comparisons and still allowed for more power in analyzing differences between the groups.…”
Section: Discussioncontrasting
confidence: 47%
“…In addition, HCAHPS analysis models adjust for possible nonresponse bias resulting from differential response rates across hospitals. 25 7. There are faster, cheaper, and more customized ways to survey patients than the standardized approaches mandated by federal accountability initiatives.…”
Section: Patient Experience Scores May Be Confounded By Factorsmentioning
confidence: 99%
“…[2][3][4][5] The item is also used as a case mix variable for patient experiences with care measures. 6 The Patient-Reported Outcomes Measurement Information System (PROMIS ® ) project was funded by the National Institutes of Health (NIH) in 2004 with the objective of developing, evaluating, and disseminating publicly available survey items assessing self-reported generic health (www.nihpromis. gov).…”
mentioning
confidence: 99%